Measurement of CH3D on Titan at submillimeter wavelengths - Thelen, A; Nixon, C; Cordiner, M; Charnley, S; Irwin, P; Kisiel, Z (IOP Publishing, 2019)
We present the first radio/submillimeter detection of monodeuterated methane (CH3D) in Titan's atmosphere, using archival data from of the Atacama Large Millimeter/submillimeter Array (ALMA). The J K = 21−11 and J K = 20−10 transitions at 465.235 and 465.250 GHz (~0.644 mm) were measured at significance levels of 4.6σ and 5.7σ, respectively. These two lines were modeled using the Non-linear optimal Estimator for MultivariatE spectral analySIS (NEMESIS) radiative transfer code to determine the disk-averaged CH3D volume mixing ratio = 6.157 × 10−6 in Titan's stratosphere (at altitudes >130 km). By comparison with the CH4 vertical abundance profile measured by Cassini–Huygens mass spectrometry, the resulting value for D/H in CH4 is (1.033 ± 0.081) × 10−4. This is consistent with previous ground-based and in situ measurements from the Cassini–Huygens mission, though slightly lower than the average of the previous values. Additional CH3D observations at higher spatial resolution will be required to determine a value truly comparable with the Cassini–Huygens CH4 measurements, by measuring CH3D with ALMA close to Titan's equator. In the post-Cassini era, spatially resolved observations of CH3D with ALMA will enable the latitudinal distribution of methane to be determined, making this an important molecule for further studies.